Pengaruh Return Saham dan Pengetahuan Investasi terhadap Minat Investasi Mahasiswa dengan Modal Minimal Investasi sebagai Variabel Mediasi (Studi pada Galeri Investasi Syariah UIN Maulana Malik Ibrahim Malang) - Herdiana Satya Putra; Muhammad Sulhan (Ekonomis: Journal of Economics and Business, 2023)
This study examines the variables of stock return and investment knowledge on investment interest of students with minimum capital as a mediating variable at UIN Maulana Malik Ibrahim Malang Sharia Investment Gallery with a sample of 105 members. This research uses quantitative methods. The results of this study indicate that the instrument data items are declared valid and reliable. The path coefficient test shows that the effect between the variables of stock returns and investment knowledge on minimum capital is positive, and the effect between investment knowledge and minimum capital on investment interest is positive, while the effect of stock returns on investment interest is negative. The hypothesis test shows that stock returns have no significant effect on investment intention, investment knowledge has a significant effect on investment interest, minimum capital has a significant effect on investment interest, stock returns have no significant effect on minimal capital, investment knowledge has a significant effect on minimal capital, stock returns have no effect significantly to investment interest through minimum capital, investment knowledge has a significant effect on investment interest through minimal capital. This shows that stock returns are not the main reason that makes students interested in investing but rather the investment knowledge received and the minimum capital required which is the reason for student investment interest.